Kajian Eksegetis Tentang Relasi antara Penderitaan dalam Ayub 1-21 dan Kedaulatan Ilahi dalam Tradisi Kenabian Perjanjian Lama - Mersiana Pongtasik; Imelia Yanti Parab; Ananda Astrid Aulia (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2026)
This study examines the relationship between suffering in Job 1–21 and God's sovereignty in the Old Testament. The problem arises from the tension between the theology of retribution that links suffering to sin and the reality that the righteous can also suffer. Job is a key figure in understanding this theological dilemma. This study uses a qualitative method with a biblical exegetical approach through analysis of historical context, literary structure, and theological meaning. The primary data comes from the text of Job 1–21, supported by relevant theological literature. The analysis is conducted descriptively and analytically to find the relationship between suffering and God's sovereignty. The results show that Job's suffering is not a direct result of sin, but rather occurs within the scope of God's sovereignty that transcends human understanding. This text also critiques the rigid understanding of the theology of retribution and emphasizes that faith is rooted in trust, not merely rational understanding. Job's perseverance demonstrates that suffering can be a means of faith growth as well as a test that deepens humanity's relationship with God. This study emphasizes that suffering is part of God's sovereign plan and encourages believers to remain faithful and persevere amidst the uncertainties and struggles of life.